1998
DOI: 10.1007/s004280050258
|View full text |Cite
|
Sign up to set email alerts
|

Chronic glandular bronchitis in young individuals residing in a metropolitan area

Abstract: A study of 161 Los Angeles County residents aged 12-28 years old who had died sudden violent deaths showed frequent and severe chronic glandular bronchitis (CGB), that is to say grade > or =5 (0-10) chronic inflammation involving at least one, half or more, and all submucosal glands in 53.4%, 21%, and 4.4% of the main stem bronchi, respectively. The mean plasma cell/gland/bronchus was high (> or =5) for 22 subjects (13.7%), while only 2 bronchi (1.2%) had a correspondingly high lymphocyte mean (P<0.001). Of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Among the components of air pollution, particulate matter (PM) has been consistently associated with chronic respiratory symptoms and pulmonary function alterations in children (3,10,15,17,18). In addition, data provided by autopsy studies reveal that young adults living in areas with high ambient levels of inhalable particles have pathologic alterations of airways and distal pulmonary parenchyma (20)(21)(22). We reasoned that the role of PM in causing alterations in pulmonary development would be better evaluated in animal models, because confounding variables such as exposure assessment, co-morbidity, and individual variability can be controlled.…”
mentioning
confidence: 99%
“…Among the components of air pollution, particulate matter (PM) has been consistently associated with chronic respiratory symptoms and pulmonary function alterations in children (3,10,15,17,18). In addition, data provided by autopsy studies reveal that young adults living in areas with high ambient levels of inhalable particles have pathologic alterations of airways and distal pulmonary parenchyma (20)(21)(22). We reasoned that the role of PM in causing alterations in pulmonary development would be better evaluated in animal models, because confounding variables such as exposure assessment, co-morbidity, and individual variability can be controlled.…”
mentioning
confidence: 99%
“…Our earlier subjective measurements of chronic inflammation of airways [11,38] and airspaces [10] of comparable groups found eosinophilia in 10% and chronic lung inflammation in approximately one of four. In some of those subjects, lung remodeling was observed that included peribronchiolar fibrosis, alveolar airspace derangement, and/or parenchymal scarring [10].…”
Section: Covert Chronic Lung Inflammation and Eosinophiliamentioning
confidence: 97%
“…Discrete focal inflammation of clinically normal salivary glands has also been noted [16]. Finally, asymptomatic airway inflammation is common and can be elicited by ubiquitous stimuli such as smoke or smog [17,18]. Herpesviruses must have evolved a way of migrating to such mucosal sites, perhaps by taking advantage of inflammatory cells that go there naturally.…”
Section: What Do Herpesviruses Chlamydiae and Parvovirus B19 Have Inmentioning
confidence: 99%